Bimatoprost 0.03% for the Treatment of Eyebrow Hypotrichosis. Issue 5 (May 2016) - Carruthers, Jean; Beer, Kenneth; Carruthers, Alastair; Coleman, William P.; Draelos, Zoe Diana; Jones, Derek; Goldman, Mitchel P.; Pucci, Michael L.; VanDenburgh, Amanda; Weng, Emily; Whitcup, Scott M.
Abstract : BACKGROUND: Eyebrow loss may have substantial negative functional and social consequences. OBJECTIVE: Evaluate the safety and efficacy of bimatoprost 0.03% in subjects with eyebrow hypotrichosis. METHODS: This multicenter, double-masked study randomized adult females or males with eyebrow hypotrichosis to receive bimatoprost 0.03% twice (BID) or once daily (QD) or vehicle BID for 7 months. Primary endpoint was overall eyebrow fullness at Month 7. Secondary endpoints included eyebrow fullness (mm 2 ), darkness (intensity units), and subject satisfaction with treatment. Safety was also assessed. RESULTS: At Month 7, the proportion of subjects with improvement was significantly higher in bimatoprost groups versus vehicle (both, p < .001). Improvements occurred in both bimatoprost groups versus vehicle after Month 1 and continued through follow-up; eyebrow fullness and darkness improved as early as Months 2 and 1, respectively (both, p < .001). Greater satisfaction was reported with bimatoprost versus vehicle at Month 2 and all subsequent time points. Overall, 38.1%, 42.4%, and 35.5% of subjects in the bimatoprost BID, QD, and vehicle groups, respectively, experienced ≥1 treatment-emergent adverse event (TEAE). Most frequent TEAEs were similar across groups. No skin or iris hyperpigmentation or conjunctival hyperemia occurred. CONCLUSION: Bimatoprost 0.03% BID and QD is safe, well tolerated, and effective for eyebrow hypotrichosis.